(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Language is not merely a tool for communication but also a reflection of cultural norms, values, and unconscious biases. The way people speak, the words they choose, and even their nonverbal cues are deeply embedded in cultural frameworks that often operate outside conscious awareness. This article explores the unconscious aspects of linguistic communication, examining how cultural background shapes language use, perception, and interaction without speakers realizing it.